Pengaruh Arsitektur Kolonial pada Bangunan Rumah Sakit St. Carolus Jakarta - Dewik Untarawati (AMERTA, 2025)
Abstract, The Influence of Colonial Architecture on The St. Carolus Hospital Building in Jakarta, The issue of colonial architecture in hospital buildings in Indonesia has rarely been explored in historical studies. One notable example is the architecture of St. Carolus Hospital in Jakarta, which holds both distinctive features and significant historical value. St. Carolus Hospital is the first Catholic hospital in Jakarta, founded by the Apostolic Vicar of Batavia in 1919. The hospital was designed in a colonial architectural style by Simon Snuyf, with assistance from F.J.L. Ghijsels. This study aims to analyze the influence of colonial architecture on the design and function of St. Carolus Hospital, as well as to examine the transformation of its architectural elements from the colonial period to the present day. The research employs a historical method with an archaeological approach, using typological and morphological analysis techniques based on photographic sources. The data is supported by literature studies from colonial newspapers, books, and academic journals. The findings reveal that St. Carolus Hospital was originally designed in a transitional architectural style. Over time, the building has transformed into a modern facility while retaining key elements of its colonial architectural heritage. Keywords:  Hospital, St. Carolus, Architecture, Colonial Abstrak, Isu mengenai arsitektur kolonial pada bangunan rumah sakit di Indonesia jarang sekali dibahas dalam studi Sejarah, salah satunya adalah arsitektur Rumah Sakit St. Carolus Jakarta yang memiliki keunikan dan nilai sejarah yang panjang. Rumah Sakit St. Carolus merupakan rumah sakit katolik pertama di Jakarta yang didirikan oleh Vikaris Apostolik Batavia pada tahun 1919. Rumah sakit ini dirancang dengan gaya arsitektur kolonial oleh Simon Snuyf, dengan bantuan F.J.L. Ghijsels. Studi ini bertujuan untuk menganalisis pengaruh arsitektur kolonial pada bangunan Rumah Sakit St. Carolus terhadap desain dan fungsi serta menjelaskan perubahan arsitektur Rumah Sakit St. Carolus dari masa kolonial hingga sekarang. Penelitian ini menggunakan metode historis dengan pendekatan arkeologis, melalui teknik analisis tipologi dan morfologi yang didasarkan pada sumber fotografi. Data penelitian ini didukung oleh studi literatur dari surat kabar kolonial, buku, dan jurnal akademik. Penelitian ini mengungkapkan bahwa Rumah Sakit St. Carolus pada awalnya dirancang dengan gaya arsitektur transisi. Seiring waktu, bangunan ini telah berubah menjadi fasilitas modern namun tetap mempertahankan elemen-elemen penting dari warisan arsitektur kolonialnya. Kata Kunci: Rumah Sakit, St. Carolus, Arsitektur, Kolonial